KENDALI OPTIMAL PERTUMBUHAN POPULASI ECENG GONDOK DENGAN IKAN GRASS CRAP DAN PEMANENAN - Fitroh Resmi; Aris Alfan; Slamet Ifandi (Jurnal Matematika Sains dan Teknologi, 2019)
Water hyacinth is a wild aquatic plant that grows quickly. The growth of water hyacinth need to be controled to prevent the flood and not to disturb paddy irrigation channels. Grass carp as herbivorous fish is used as natural predator to reduce the population of water hyacinth. The interaction between water hyacinth and grass carp is modeled using the prey-predator system. In this model there are harvest factors and predation factors using Holling type III. The optimal control problem is applied to minimize the mass of water hyacinth and harvest efforts of water hyacinth and maximize the mass of grass carp. The solution uses the Pontryagin Principle. The result is that the harvesting of water hyacinth and the grass carp can minimize the water hyacinth biomass at the end of time. Eceng gondok merupakan tanaman liar di perairan yang tumbuh dengan cepat. Pertumbuhannya perlu dikendalikan agar tidak menyebabkan banjir dan tidak mengganggu saluran irigasi persawahan. Ikan grass carp sebagai ikan herbivora digunakan sebagai predator alami untuk mengurangi populasi eceng gondok. Hubungan antara eceng gondok dan ikan grass carp dimodelkan dengan menggunakan sistem prey-predator. Pada model ini terdapat faktor pemanenan dan faktor predasi menggunakan Holling tipe III. Masalah kendali optimal diterapkan dengan tujuan untuk meminimumkan massa eceng gondok dan usaha pemanenan eceng gondok serta memaksimumkan massa ikan grass carp. Penyelesaiannya menggunakan Prinsip Pontryagin. Hasilnya dengan adanya usaha pemanenan eceng gondok dan pengadaan ikan grass carp dapat meminimumkan biomassa eceng gondok di waktu akhir.